Androgen receptor suppresses prostate cancer metastasis but promotes bladder cancer metastasis via differentially altering miRNA525-5p/SLPI-mediated vasculogenic mimicry formation. (31st March 2020) - Yang, Zhao; Chen, Jiaqi; Xie, Hongjun; Liu, Tianjie; Chen, Yule; Ma, Zhenkun; Pei, Xinqi; Yang, Wenjie; Li, Lei
Abstract: Early studies suggest that the androgen receptor (AR) may play differential roles in influencing prostate cancer (PCa) and bladder cancer (BCa) metastasis, but the underlying mechanisms remain unclear. Here, we found that the AR might function via differentially altering vasculogenic mimicry (VM) formation to either decrease PCa metastasis or increase BCa metastasis. Mechanism dissection showed that the AR could differentially alter the expression of the VM marker SLPI through miR-525-5p to regulate SLPI; moreover, it could either increase miR-525-5p transcription in PCa or decrease it in BCa via binding to different androgen-response-elements (AREs) located at different positions in the miR-525 precursor promoter. Further, results from liquid chromatography–mass spectrometry (LC-MS) showed that the co-factors of AR in PCa and BCa are NFIX and HDAC2, respectively. Together, these results provide the first detailed mechanism of how the AR can differentially alter PCa and BCa metastasis; thus, targeting the newly identified AR-miR-525-5p-SLPI axis may help suppress metastasis. Highlights: AR can differentially alter VM formation in PCa and BCa via altering SLPI expression. AR modulates SLPI expression via altering miRNA-525-5p expression. AR binds to different AREs on the miR-525-5p promoter region in PCa and BCa. NFIX in PCa and HDAC2 in BCa were considered to be the AR co-factors that could possibly impact the activity of miR-525-5p.